Oral carnosine supplementation prevents vascular damage in experimental diabetic retinopathy - Pfister, Frederick; Riedl, Eva; Wang, Qian; vom Hagen, Franziska; Deinzer, Martina Ulrike; Harmsen, Martin Conrad; Molema, Grietje; Yard, Benito A.; Feng, Yuxi; Hammes, Hans-Peter (Cellular physiology and biochemistry, 2011)
BACKGROUNDS/AIMS: Pericyte loss, vasoregression and neuroglial activation are characteristic changes in incipient diabetic retinopathy. In this study, the effect of the antioxidant and antiglycating dipeptide carnosine was studied on the development of experimental diabetic retinopathy. - MATERIALS/METHODS: STZ-induced diabetic Wistar rats were orally treated with carnosine (1g/kg body weight/day). Retinal vascular damage was assessed by quantitative morphometry. Retinal protein extracts were analyzed for markers of oxidative stress, AGE-formation, activation of the hexosamine pathway and changes in the expression of Ang-2, VEGF and heat shock proteins Hsp27 and HO-1. Glial cell activation was analyzed using Western blot analysis and immunofluorescence of GFAP expression and retinal neuronal damage was histologically examined. - RESULTS: Oral carnosine treatment prevented retinal vascular damage after 6 months of experimental hyperglycemia. The protection was not caused by ROS- or AGE-inhibition, but associated with a significant induction of Hsp27 in activated glial cells and normalization of increased Ang-2 levels in diabetic retinas. A significant reduction of photoreceptors in retinas of carnosine treated animals was noted. - CONCLUSION: Oral carnosine treatment protects retinal capillary cells in experimental diabetic retinopathy, independent of its biochemical function. The vasoprotective effect of carnosine might be mediated by the induction of protective Hsp27 in activated glial cells and normalization of hyperglycemia-induced Ang-2.